2010
DOI: 10.4049/jimmunol.0903273
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Receptor Regulates Neutrophil Functions and Innate Immunity to Leishmania Parasites

Abstract: Type I IFNs exert diverse effector and regulatory functions in host immunity to viral and nonviral infections; however, the role of endogenous type I IFNs in leishmaniasis is unclear. We found that type I IFNR-deficient (IFNAR−/−) mice developed attenuated lesions and reduced Ag-specific immune responses following infection with Leishmania amazonensis parasites. The marked reduction in tissue parasites, even at 3 d in IFNAR−/− mice, seemed to be indicative of an enhanced innate immunity. Further mechanistic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
74
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 54 publications
9
74
0
1
Order By: Relevance
“…Other studies of protozoan parasite infections suggest a requirement for IFN-I in mediating innate and adaptive immune responses [38][39][40]. Our study is the first to demonstrate that IFN-I impedes primary, adaptive immune responses during infection with a protozoan parasite.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Other studies of protozoan parasite infections suggest a requirement for IFN-I in mediating innate and adaptive immune responses [38][39][40]. Our study is the first to demonstrate that IFN-I impedes primary, adaptive immune responses during infection with a protozoan parasite.…”
Section: Discussionsupporting
confidence: 58%
“…By employing IFN-aR1 À/À mice, which are deficient in IFN-I signalling, we clearly showed that IFN-I indirectly suppressed CD4 1 T-cell responses during blood-stage infection, and impeded control of parasites in two different murine blood-stage malaria models. IFN-I are known to play a crucial role in protection against viruses [36,37], but their role in Plasmodium infections and other protozoan parasite infections has not been extensively studied [38][39][40]. The role of IFN-I during blood-stage Plasmodium infection is not clear, although early studies detected IFN activity in the blood after Plasmodium infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that L. amazonensis parasites induce IFN1-b expression via RNAdependent protein kinase (PKR) in a TLR2-dependent manner (3) and that IFN1-b favors parasite growth. In addition, IFN1-a receptor (IFNAR) signaling favors L. amazonensis infection in mice (4). Another component of host immune defense subverted by L. amazonensis is the reactive oxygen species (ROS) defense mechanism.…”
mentioning
confidence: 99%
“…Treatment of infected human macrophages with poly I:C promotes parasite replication in a PKR-dependent manner, although the role of type I IFN was not formally established. In vivo, L. amazonensis-infected Ifnar1 2/2 mice show reduced parasite load, as well as decreased pathology, compared with WT mice (152). The increased resistance is associated with enhanced recruitment of neutrophils.…”
Section: Leishmaniamentioning
confidence: 97%
“…The increased resistance is associated with enhanced recruitment of neutrophils. In this case, neutrophils are believed to mediate pathogen killing by releasing enzymes, such as elastase and myeloperoxidase (152).…”
Section: Leishmaniamentioning
confidence: 99%